MELAWAN EKSPLOITASI TUBUH ANTARA FEMINISME BARAT DAN ISLAM - Ayub (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
This paper discusses about one of the major themes in the movement and thought in Western feminism namely the issue of the exploitation of women's bodies. The modern feminism was born in the context of Western civilization. This paper discussion starts from a review of how Western society treats women and an effort from feminism in changing the community. Then, this paper will explain the main point about how come the feminism stuck in a similar pattern to their opponent society. Islam will describe a unique way of looking at this issue.